2007
DOI: 10.1061/(asce)0733-9453(2007)133:2(81)
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Back-Propagation Artificial Neural Network to Regional Grid-Based Geoid Model Generation Using GPS and Leveling Data

Abstract: The height difference between the ellipsoidal height h and the orthometric height H is called undulation N. The key issue in transforming the global positioning system ͑GPS͒-derived ellipsoidal height to the orthometric height is to determine the undulation value accurately. If the undulation N for a point whose position is determined by a GPS receiver can be estimated in the field, then the GPS-derived three-dimensional geocentric coordinate in WGS-84 can be transformed into a local coordinate system and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The test results indicated that the accuracy of the estimated geometric undulation interpolation that used the LS-SVM was in the order of 1.5 cm. Based on these results, the estimated undulation accuracy attained using the LS-SVM was superior to that attained using the curve fitting and BPANN methods (LIN, 2007) by an order of 2-4 cm in the same test area.…”
Section: Study Results and Analysismentioning
confidence: 86%
See 2 more Smart Citations
“…The test results indicated that the accuracy of the estimated geometric undulation interpolation that used the LS-SVM was in the order of 1.5 cm. Based on these results, the estimated undulation accuracy attained using the LS-SVM was superior to that attained using the curve fitting and BPANN methods (LIN, 2007) by an order of 2-4 cm in the same test area.…”
Section: Study Results and Analysismentioning
confidence: 86%
“…Numerous researchers (ABDALLA et al, 2011, KAO et al, 2011, LIN, 2007, You, 2006 have investigated combined methods for improving local geoids, using GPS and geodetic leveling data. These scholars have presented multiple useful tools and interpolation methods.…”
Section: The Least Squares Support Vector Machinementioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have investigated the development of suitable local geoid undulation models by applying various fitting methods to measurements of ellipsoidal height h and leveling orthometric height H obtained using global positioning systems (GPSs) (Odera et al, 2014;Abdalla et al, 2011;Abdalla and Fairhead, 2011;Akcin and Celik, 2013;Abdalla, 2009;Featherstone et al, 2004;Kao et al, 2014 ;Kao, 2006;Kotsakis and Sideris, 1999;Kao and Bethel, 1992(a); Kao and Bethel, 1992(b) ;Ning, 2015;Lin, 2007;Tranes et al, 2007;Kiamehr, 2006;Ustun and Demirel, 2006;You, 2006;Yang and Chen, 1999). The geoid of each position in a location can be calculated to determine H for each position.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning application of soft computing technique Kavzoglu and Saka 2005 [6] and Lao-Sheng Lin 2006 [7] employed artificial neural network (ANN) for approximating the GPS/levelling geoid instead of the corrector surface itself. Both of them applied feed-forward ANN with the standard sigmoid activation functions and different number of hidden layers.…”
Section: Introductionmentioning
confidence: 99%